The Historical Rawls: Introduction - Smith, S; Bejan, TM; Zimmermann, A (Cambridge University Press, 2021)
John Rawls (1921–2002) and his work are now squarely a subject for history. In the more than fifteen years since his death, a rich body of scholarship has emerged which attempts, in different ways, to understand the nature, development, and impact of Rawls's thought from a variety of historical perspectives. With 2021 marking fifty years since A Theory of Justice (1971) was first published, this special forum examines what we here call the “historical Rawls.”